(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
One of the unsolved problems of modern surgery is the treatment of combined injuries of blood vessels and limb bones. Combined vascular and osteoarticular injuries account for 4.3-10% of the total number of limb fractures. When treating this group of patients, surgeons often face a dilemma — to perform primary amputation or try to save the limb. Despite success in surgical treatment of patients with combined injuries of the arteries and bones of the extremities, there is a high frequency of amputations (3-60%) and deaths.